Climate‐driven range shifts are stochastic processes at a local level: two flying squirrel species in Maine. Issue 2 (26th February 2016) - Wood, Connor M.; Witham, Jack W.; Hunter, Malcolm L.
Abstract: Numerous directional range shifts have been linked to climate change, but mechanistic explanations are frequently absent. In North America, southern flying squirrel ( Glaucomys volans ) range has expanded northward as a result of climate change, and northern flying squirrel ( G. sabrinus ) range has shifted north, likely in response to competition. We tracked both species abundances as well as climate, food availability, and forest structure over 31 yr, and found complete species turnover from G. sabrinus to G. volans in 18 yr. We tested multiple generalized least squares models of each species' abundance over time. The top model for G. sabrinus indicated that abundance was likely shaped by the arrival of G. volans, a competitor and known vector of a pathological nematode, food, and modest anthropogenic changes to forest structure; the top model for G. volans suggested that warm winters coinciding with high mast years likely facilitated the initial establishment of G. volans, whereas positive density dependence likely shaped subsequent population dynamics. The only significant change to local climate was an increase in minimum summer temperature, which would enhance the survival of Strongyloides robustus, the nematode carried by G. volans and detrimental to G. sabrinus . This complex suite of interactions suggests that at a local level, range shifts may be a largely stochastic process permitted by the temporal coincidence of multiple species‐ and site‐specific factors.